Penerapan Metode Weighted Aggregated Sum Product Assessment pada Pemilihan Instruktur Terbaik dalam Pembelajaran Mengemudi Mobil: Array - Silalahi, Ade Tina; Lestari, Yuyun Dwi; Annisah, Yessi Fitri (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2021)
One form of non-formal education is a course where many people learn cars with the aim of being able to master it in a short time. The more people who want to take car driving courses, the more Institutions will provide the best instructors for the community in driving cars. There are many criteria to determine the best instructor in car driving learning such as length of work, discipline, friendliness which are reasons to determine the best driving instructor. Therefore, the best driving instructor recommendation system is needed for people who want to learn to drive a car is very important to create customer satisfaction. This study will build a decision support system using the waspas method with the aim of being able to implement the Weighted Aggregated Sum Product Assessment method in determining the best car driving instructor which is unacceptable to prospective customers who want to learn to drive a car. The system will be built with the PHP and MySQL programming languages ​​as the database.